Peces fósiles de la localidad lomas de Siquirres, cauce del Río Reventazón, formación Río Banano, Mioceno Superior, provincia de Limón, Costa Rica - Laurito, César A. (2011)
Remains of selachians (sharks and rays) and other icthiolites have been collected from the Upper Mio- cene locality of Lomas de Siquirres. A new record of fossil species of shark is described for Central America and the Caribbean Region: Carcharhinus albimarginatus (Rüpel, 1837). The fauna of the Río Banano Formation is notable for the Tethysian affinity with the paleomediterranean faunas.